Rzeźby zdegradowane. Twórczość Romana Stańczaka wobec transformacji ustrojowej po 1989 roku - Dorota Michalska (Miejsce)
Roman Stańczak’s work from the years 1990–1996 can be perceived as a manifestation of multilevel processes of degradation that struck some of the regions and social groups in Poland as a result of Poland’s post-1989 transition from centrally planned to capitalist economy. Intensifying throughout the 1990s, the degradation was a complex phenomenon: both material and psychological, both social and class-based. My main theoretical frame to interpret Stańczak’s work in this light is Tomasz Rakowski’s book ”Hunters, Gatherers, and Practitioners of Powerlessness. An Ethnography of the Degraded in Post-Socialist Poland”, published in 2009. The publication is a fruit of field research in the areas of Szydłowiec, Radom and Wałbrzych, amongst other towns – the territories that after 1989 suffered the worse unemployment in Poland and the ensuing poverty. Rakowski describes economic and cultural practices (referred to by the scholar as ‘survival strategies’) that emerged in some social groups facing the loss of former income sources. In the essay, I outline a series of similarities and parallels that can be discerned between Stańczak’s artistic practice and the world of ‘hunters, gatherers, practitioners’, described by Rakowski.